(untitled) (Monaldi Archives for Chest Disease, 2015)
In HIV infected patients an increased incidence of cardiac events has been reported since the introduction of highly active antiretroviral therapy (HAART). Antiretroviral drugs’ regimens are, in fact, associated with several metabolic side effects, such as dyslipidemia, impaired glucose metabolism and abnormal body fat distribution, that increase cardiovascular risk of HIV subjects. In addition, HIV infection itself, the chronic inflammatory status and the frequent presence in this population of traditional risk factors contribute to an higher incidence of cardio and cerebrovascular events. In last years several studies showed the occurrence of carotid vascular impairment in patients treated with protease inhibitors (PI). Similarly the DAD Study reported an increase of 26% of the risk of myocardial infarction in patients on HAART and that this risk was independently associated with longer exposure to PI, after multivariate adjustments. A correct evaluation of the metabolic status before starting HAART and an adequate control of drugs-related metabolic abnormalities may reduce the incidence of cardiac events and still improve HIV patients prognosis. This review will focus on the metabolic effects of antiretroviral drugs and on the contribution of combination antiretroviral therapy on cardiovascular risk.